2019
DOI: 10.1101/834697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Within Visit Test-Retest Reliability of EEG Profiles in Children with Autism Spectrum Disorder and Typical Development

Abstract: 37 Biomarker development is currently a high priority in neurodevelopmental disorder research. For 38 many types of biomarkers (particularly biomarkers of diagnosis), reliability over short time periods is 39 critically important. In the field of autism spectrum disorder (ASD), resting electroencephalography 40 (EEG) power spectral densities (PSD) are well-studied for their potential as biomarkers. Classically, 41 such data have been decomposed into pre-specified frequency bands (e.g., delta, theta, alpha, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although we focus on ADHD risk, excitatory/inhibitory imbalance and differences in the aperiodic exponent of the power spectrum have been observed in other neurodevelopmental disorders as well. Racz et al (2021) identified a trend toward shallower exponents in a small sample of adults with schizophrenia as compared to typically developing adults, and there is interest in whether disruptions appear in autism spectrum disorder (Levin et al, 2020). Crucially, as others have highlighted (Donoghue, Haller, et al, 2020;Mamiya et al, 2021;Voytek & Knight, 2015), the excitatory/inhibitory balance is critical for optimal synaptic plasticity and neuronal developmental, generally, and for maximizing signal to noise ratio in neural circuitry, specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Although we focus on ADHD risk, excitatory/inhibitory imbalance and differences in the aperiodic exponent of the power spectrum have been observed in other neurodevelopmental disorders as well. Racz et al (2021) identified a trend toward shallower exponents in a small sample of adults with schizophrenia as compared to typically developing adults, and there is interest in whether disruptions appear in autism spectrum disorder (Levin et al, 2020). Crucially, as others have highlighted (Donoghue, Haller, et al, 2020;Mamiya et al, 2021;Voytek & Knight, 2015), the excitatory/inhibitory balance is critical for optimal synaptic plasticity and neuronal developmental, generally, and for maximizing signal to noise ratio in neural circuitry, specifically.…”
Section: Discussionmentioning
confidence: 99%